The Application of Mobile fNIRS in Marketing Research—Detecting the “First-Choice-Brand” Effect - Krampe, Caspar; Gier, Nadine Ruth; Kenning, Peter (Frontiers in Human Neuroscience, 2018)
Recent research in the field of “neuro-marketing” shows promise to substantially increase knowledge on marketing issues for example price-perception, advertising efficiency, branding and shopper behaviour. Recently, an innovative and mobile applicable neuroimaging method has been proposed, namely functional near-infrared spectroscopy (fNIRS). However, this method is, in the research field of marketing, still in its infancy and is, consequently, lacking substantial validity. Against this background, this research work applied a convergent validity approach to challenge the validity of (mobile) fNIRS in the field of “neuro-marketing” and consumer neuroscience. More precisely, we aim to replicate a robust and well-investigated neural effect previously detected with fMRI—namely the “first-choice-brand” effect—by using mobile fNIRS. The research findings show that mobile fNIRS appears to be an appropriate neuroimaging method for research in the field of “neuro-marketing” and consumer neuroscience. Additionally, this research work presents guidelines, enabling marketing scholars to utilise mobile fNIRS in their research work.